The Influence of Human Resource Quality, Professionalism, and Work Discipline on Work Performance and Organizational Commitment at CV Oktaviana Tas Grosir Mojokerto - Winda Dwi Octavia; Slamet Riyadi; Sumiati Sumiati (Journal of Social Research, 2025)
Based on results overlay visualization from research mapping analysis using applications VOS-Viewer, it appears that the research trends are related work performance (work performance) in the last five years is still relatively minimal. In fact, this topic has great potential for further development considering its relevance in the ever-changing world of work. This research aims to analyze the influence of Human Resource Quality, Professionalism and Work Discipline on Work Performance and Organizational Commitment. This research method is quantitative with an explanatory research approach, which aims to verify the hypothesis that has been determined by the researcher. The population in this study were employees of CV Oktaviana Tas Grosir Mojokerto, total 70 employees using a saturated sample. Hypothesis testing in this research was carried out using an approach Structural Equation Model (SEM) based Partial Least Square (PLS). Based on the 7 direct influence hypotheses processed in this research, there are 2 hypotheses which state that the effect is not significant while the other 5 hypotheses state that the effect is significant. The results of this research show that Human Resources Quality and Professionalism partially have an insignificant effect on Organizational Commitment. Meanwhile, Work Discipline has a significant positive effect on Organizational Commitment. Then Professionalism, Work Discipline and Organizational Commitment partially have a significant positive effect on Work Performance. Meanwhile, Human Resources Quality has a significant negative effect on Work Performance.